Networking early modern Irish women. Issue 170 (November 2022) - Bourke, Evan
Abstract: Over the last decade, network analysis has developed as an approach within digital humanities as a wider array of tools has become available to humanities scholars, and these approaches are now beginning to make an impact on the disciplines of history and English. This article presents an overview of different ways of approaching network analysis. It assesses recent projects to see how they accounted for gender in their datasets and what can be learnt about early modern women from these projects. It then looks at how projects in Ireland are engaging with network analysis, discussing the approaches used by RECIRC and introducing MACMORRIS's analysis of the Dictionary of Irish biography (D.I.B.) and the Bardic Poetry Database (B.P.D.), looking at how the latter is attempting to overcome the unconscious gender bias inherent in the D.I.B.'s selection of early modern lives from the period between 1541 and 1660. Finally, it points to some of the wider issues we as scholars face when engaging with this methodology, such as access to the required training and collaboration, arguing that while these are not unique challenges to the study of gender history in Ireland, they are important debates that can enhance scholarship in the field.